Cyclopropenium-Activated DMSO for Swern-Type Oxidation - Guo, Tianfo; Gao, Yu; Li, Zhenjiang; Liu, Jingjing; Guo, Kai (Synlett, 2019)
Swern oxidation is widely used to convert alcohols into their corresponding carbonyl compounds. However, the conventional method with use of the volatile oxalyl chloride as an activator requires the reaction to be conducted below −60 °C. We discovered that 3,3-dichloro-1,2-diphenylcyclopropene (DDC) can be used as a new activator for Swern-type oxidations of alcohols, which can be conducted at −20 °C. This new protocol features mild and fast reactions with easy operation. Furthermore, the activator DDC is easy to handle, and diphenylcyclopropenone can be recovered quantitively. This new type of Swern oxidation shows a broad scope of substrates including benzylic, allylic, aliphatic, and biobased alcohols, and gives high yields of up to 93%.
Keywords: alcohols; carbonyl compounds; cyclopropenium ion; geminal dichloro compounds; Swern oxidation